RELIABILITY EVALUATION OF OVERHEAD POWER TRANSMISSION SYSTEMS TO SUPPORT ELECTRIC RAILWAY OPERATIONS IN THE JABODETABEK AREA - Prasetiyo, Edwin Rozzaq; Virdyawan, Vani; Rachmildha, Tri Desmana (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Overhead catenary system (OCS) is a vital infrastructure for the operation of electric railway trains as it delivers electrical power from the traction substation to the train pantograph. Increasing train trips in urban areas imposes additional mechanical and electrical loads on OCS components, thus demanding more frequent and accurate maintenance. This study introduces a risk-based reliability evaluation approach for critical OCS components by integrating risk matrix analysis with Anderson-Darling distribution fitting for failure and repair data. The methodology enables precise reliability and availability assessment of each component, comparing results to the operational targets. Findings show that contact wire, messenger wire, and hanger have reliability values below the company’s standard, whereas feeder wire and transmission poles exceed the targets. The proposed approach provides a data-driven framework to support condition-based maintenance planning and improve system readiness.